Capacity for an inadequacy : a discussion of the performative body in video space : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Irving, Melissa (Massey University, 2013)
This thesis explores how video documentation can reveal and transcend the distance in time and space between the event of a recording of a performance and the secondary audience, creating an awareness of the processes undertaken. It discusses the ontology of the camera operator in duality with site responsivity and the challenge generated by displacing a movement discipline.
Keywords: Experimental films; Performance on video; Performance and audience; Video art installation